2014
DOI: 10.1111/jne.12171
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic Co‐Regulation of Kisspeptin, Neurokinin B and Dynorphin in the Hypothalamus of a Seasonal Rodent

Abstract: In many species, sexual activity varies on a seasonal basis. Kisspeptin (Kp), a hypothalamic neuropeptide acting as a strong activator of gonadotrophin-releasing hormone neurones, plays a critical role in this adaptive process. Recent studies report that two other neuropeptides, namely neurokinin B (NKB) and dynorphin (DYN), are co-expressed with Kp (and therefore termed KNDy neurones) in the arcuate nucleus and that these peptides are also considered to influence GnRH secretion. The present study aimed to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Some peptides may coexist in the same neurons (Swanson, 1987 ). OXT and GAL, e.g., co-localize in neurons of the adult paraventricular and supraoptic nuclei (Landry et al, 1991 ; see Rossmanith et al, 1996 ; Foradori et al, 2006 ; Furutani et al, 2013 , and Bartzen-Sprauer et al, 2014 for other examples). As regards its molecular profile, this domain co-expresses Otp and interactive Sim1 / Arnt2 genes, within a Pax6 -positive and Dlx/Arx/Shh/Nkx2.1 -negative background (Figure 1C ; Puelles et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some peptides may coexist in the same neurons (Swanson, 1987 ). OXT and GAL, e.g., co-localize in neurons of the adult paraventricular and supraoptic nuclei (Landry et al, 1991 ; see Rossmanith et al, 1996 ; Foradori et al, 2006 ; Furutani et al, 2013 , and Bartzen-Sprauer et al, 2014 for other examples). As regards its molecular profile, this domain co-expresses Otp and interactive Sim1 / Arnt2 genes, within a Pax6 -positive and Dlx/Arx/Shh/Nkx2.1 -negative background (Figure 1C ; Puelles et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the higher expression of ARC Kiss1 expression in sexually active Syrian hamster and ewe has to be driven by strong seasonal cues able to counteract the negative sex steroid feedback. ARC Kp neurons are known to coexpress neurokininB and dynorphin, and these two peptides in Syrian hamster (Bartzen‐Sprauer, Klosen, Ciofi, Mikkelsen, & Simonneaux, ) but only neurokininB in sheep (Weems et al., ) also exhibit seasonal changes driven by steroid‐dependant and steroid‐independent mechanisms. Further studies confirmed the occurrence of seasonal/photoperiodic variation in ARC Kp expression in a number of seasonal breeders, notably the Djungarian hamster (Greives et al., ; Rasri‐Klosen, Simonneaux, & Klosen, ), European hamster (Sáenz de Miera et al., ), Libyan jird (Boufermes et al., ), jerboa (Talbi, Klosen, Laran‐Chich, El Ouezzani, & Simonneaux, ), red deer (Barrell et al., ), and dromedary camel (Ainani et al., ) (Figure ).…”
Section: Role Of Kisspeptin In Mammalian Seasonal Reproductionmentioning
confidence: 99%
“…Unlike the preoptic cell population, KP neurons of the ARC co-synthesize KP, neurokinin B (NKB) and dynorphin (Dyn) in several species (Burke et al, 2006 ; Foradori et al, 2006 ; Goodman et al, 2007 ; Navarro et al, 2011a ; Bartzen-Sprauer et al, 2014 ), forming the basis for the “KNDy neuron” terminology (Lehman et al, 2010b ). It is only becoming recognized lately that KNDy neurons do not consist of a homogenous cell population in that co-expression of the three KNDy peptides is only partial (Cheng et al, 2010 ; Hrabovszky et al, 2010 , 2011 , 2012 ; Overgaard et al, 2014 ).…”
Section: Co-transmitters and Their Receptors In Kp Neurons Of Laboratmentioning
confidence: 99%